DURABILITY IMPROVING AGENT FOR CEMENT-HYDRAULIC-SET SUBSTANCES, METHOD OF IMPROVING SAME, AND CEMENT-HYDRAULIC SET SUBSTANCES IMPROVED IN DURABILITY - TOSHIO, SAITO; KUNIO, YANAGIBASHI; MASAHARU, SAKUTA (1997)
내용없음 The present invention provides a method for improving the durability of cement-hydraulic substances, the method decreasing the dry shrinkage of cement-hydraulic-set substances such as concrete, mortar or related substances, and increasing resistance to a repetition of the freezing and thawing of the cement-hydraulic-set substances, by the use of terminal alkyletherified compounds or terminal alkylesterified compounds of polymers having -C2H5O- and/or -C3H6O- as a repetitive unit.